Application of the module "Creation of poetic literary texts" in the written production of poetic texts in students of the 4th grade of primary school of the educational institution "Niño Jesús de Praga". Chorrillos. Lima 2017 - Berrospi Torres, Viviana (2018)
The research work was developed with the aim of analyzing whether the Module "Creation of poetic literary texts" improves written production in 4th grade "A" students of Primary Education of the Educational Institution "Niño Jesús de Praga". Chorrillos. Lima 2017 The study corresponds to a quantitative investigation, of explanatory level, and of pre-experimental design with a single group to which a previous test was applied to the Module "Creation of poetic literary texts" and finally a post-module test was applied. The sample was constituted by 19 students of 4th grade "A" of Primary Education. The data analysis processing was carried out in the statistical software SPSS version 23 and the non-parametric Mc Nemar test proved the validity of the hypothesis. The results show that before the module, no student passed the test and 100% of students disapproved, and after the module, 95% of students passed the test and 5% of students disapproved. Consequently, it was found that the Module "Creation of poetic literary texts" improved the readability, the adaptation to the theme and type of text, the textual coherence, the textual cohesion, the grammatical adequacy, the lexicon and the spelling in the written production.